Method for manufacturing electrode active material layer and method for manufacturing battery

JP2025025993AActive Publication Date: 2025-02-21TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023131305
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21
Estimated Expiration
2043-08-10

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、電極活物質層と集電体との接着力の低下を抑制するために、より簡便に、電極活物質層中にバインダーを均一に分散させることができる電極活物質層の製造方法、及びこのようにして製造された電極活物質層を含む電池の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025993000001_ABST
    Figure 2025025993000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an electrode active material layer that can more simply disperse a binder uniformly in an electrode active material layer in order to suppress a decrease in the adhesive strength between the electrode active material layer and a current collector, and a method for manufacturing a battery including an electrode active material layer manufactured in this manner.SOLUTION: The disclosed method of manufacturing an electrode active material layer includes mixing a fibrous material and a binder in a dispersion medium to obtain a preliminary slurry, mixing the preliminary slurry and an electrode active material to obtain an electrode mixture slurry, applying the obtained electrode mixture slurry to a substrate, and drying and removing the dispersion medium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an electrode active material layer and a method for producing a battery. [Background technology]

[0002] The electrode active material layer of a lithium ion battery can be produced by applying an electrode mixture slurry containing an electrode active material and a binder, etc., onto a current collector and drying the slurry. During the drying process, the binder may migrate to the surface of the slurry, reducing the amount of binder near the current collector. As a result, the adhesive strength between the electrode active material layer and the current collector decreases. In response to this, techniques have been developed to improve the adhesive strength.

[0003] For example, Patent Document 1 discloses a negative electrode comprising a current collector and a negative electrode active material layer located on at least one surface of the current collector and containing artificial graphite, single-walled carbon nanotubes (SWCNTs), and a binder polymer, the negative electrode active material layer comprising a lower layer region facing the current collector and an upper layer region facing the lower layer region and extending to the surface of the negative electrode active material layer, the content of the single-walled carbon nanotubes being 0.003 to 0.07 parts by weight based on 100 parts by weight of the lower layer region, the average diameter of the single-walled carbon nanotubes being 0.5 to 15 nm, and the upper layer region not containing single-walled carbon nanotubes (SWCNTs).

[0004] Patent Document 1 discloses that, in order to manufacture such a negative electrode, a slurry for a lower layer is manufactured by mixing artificial graphite and single-walled carbon nanotubes (SWCNTs) as negative electrode active materials, styrene butadiene rubber (SBR) as a binder polymer, water, etc., and a slurry for an upper layer is manufactured in the same manner as the slurry for the lower layer except that it does not contain SWCNTs. Patent Document 1 further discloses that the slurry for the lower layer is coated on one side of a copper (Cu)-clad thin film as a negative electrode current collector, and the slurry for the upper layer is coated on top of this slurry, and both slurries are dried. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2023-522659 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present disclosure is to provide a method for producing an electrode active material layer that can more simply disperse a binder uniformly in an electrode active material layer in order to suppress a decrease in the adhesive strength between the electrode active material layer and a current collector, and a method for producing a battery including an electrode active material layer produced in this manner. [Means for solving the problem]

[0007] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> A method for producing an electrode active material layer, comprising the steps of: mixing the fibrous material and the binder in a dispersion medium to obtain a preliminary slurry; Mixing the obtained preliminary slurry and an electrode active material to obtain an electrode mixture slurry; and The obtained electrode mixture slurry is applied to a substrate, and the dispersion medium is then dried to remove it. <Aspect 2> The fibrous material is a carbon nanotube. The method according to embodiment 1. <Aspect 3> The binder is a styrene butadiene rubber. The method according to embodiment 2. <Aspect 4> The heat source in the drying step is hot air or a laser. The method according to any one of aspects 1 to 3. <Aspect 5> Producing an electrode active material layer by the method according to any one of aspects 1 to 4; How batteries are manufactured. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a method for producing an electrode active material layer that can more simply disperse a binder uniformly in an electrode active material layer in order to suppress a decrease in the adhesive strength between the electrode active material layer and a current collector, and a method for producing a battery including an electrode active material layer produced in this manner. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1(a) is a schematic diagram showing an electrode mixture slurry prepared by a method according to an embodiment of the present disclosure, and FIG. 1(b) is a schematic diagram showing an electrode mixture slurry prepared by a method according to a comparative example of the present disclosure. [Diagram 2] FIG. 2(a) is an SEM image of an electrode active material layer produced by a method according to an embodiment of the present disclosure, and FIG. 2(b) is an SEM image of an electrode active material layer produced by a method according to a comparative example of the present disclosure. [Diagram 3] FIG. 3(a) is a cross-sectional SEM image of an electrode active material layer produced by a method according to an embodiment of the present disclosure, and FIG. 3(b) is a cross-sectional SEM image of an electrode active material layer produced by a method according to a comparative example of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] <<Method for producing electrode active material layer>> The disclosed method of producing an electrode active material layer includes mixing a fibrous material and a binder in a dispersion medium to obtain a preliminary slurry, mixing the preliminary slurry and an electrode active material to obtain an electrode mixture slurry, applying the resulting electrode mixture slurry to a substrate, and drying and removing the dispersion medium.

[0012] As described above, the electrode active material layer of a lithium ion battery can be produced by applying an electrode mixture slurry containing an electrode active material, a binder, etc., onto a current collector and drying it. During the drying, the binder may migrate to the surface of the slurry, resulting in a decrease in the amount of binder near the current collector.

[0013] In this regard, the present inventors have found that by preparing a preliminary slurry by mixing a fibrous material and a binder in a dispersion medium, and then mixing this preliminary slurry with an electrode active material to prepare an electrode mixture slurry, the binder can be uniformly dispersed in the resulting electrode active material layer. Although not intending to be bound by any theory, the reason for this is believed to be that the binder is entangled and captured by the fibrous material in the preliminary slurry, which makes it possible to suppress the binder from migrating to the slurry surface when the electrode mixture slurry prepared thereafter is dried, and as a result, the binder can be uniformly dispersed in the electrode active material layer.

[0014] That is, as shown in Fig. 1(a), in the electrode mixture slurry 1 prepared after a preliminary slurry is prepared in advance, the binder 20 is entangled and captured by the fibrous material 10, and it is considered that the binder 20 can be prevented from moving to the slurry surface. In contrast, as shown in Fig. 1(b), in the electrode mixture slurry 1 prepared without preparing a preliminary slurry, the binder 20 is not sufficiently captured by the fibrous material 10, and it is considered that the binder 20 cannot be prevented from moving to the slurry surface.

[0015] <Preliminary Slurry Preparation Step> The method of the present disclosure includes mixing a fibrous material and a binder in a dispersion medium to obtain a pre-slurry.

[0016] The fibrous material is not particularly limited as long as it has the function of entangling and capturing the binder. For example, the fibrous material may be, but is not limited to, a material such as carbon nanotubes (CNTs) or carbon nanofibers (CNFs), or a combination thereof. The carbon nanotubes may be single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), or a combination thereof.

[0017] The average diameter of the fibrous material may be 0.1 nm or more, 1.0 nm or more, 5.0 nm or more, 10 nm or more, or 15 nm or more, and may be 100 nm or less, 75 nm or less, 50 nm or less, 30 nm or less, or 25 nm or less.

[0018] The content of the fibrous material may be more than 0 parts by mass, 0.001 parts by mass or more, 0.003 parts by mass or more, or 0.005 parts by mass or more, and may be 1.0 part by mass or less, 0.1 part by mass or less, or 0.01 part by mass or less, per 100 parts by mass of the electrode mixture.

[0019] In the context of the present disclosure, the term "electrode mixture" refers to a composition that can constitute an electrode active material layer, either as it is or by further containing other components.

[0020] The binder is not particularly limited as long as it is a binder that is usually used as an electrode active material layer. For example, it may be, but is not limited to, polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HEP), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose (CMC), hydroxypropyl cellulose, regenerated cellulose, polyethylene, polypropylene, starch, butadiene rubber (BR), styrene butylene rubber (SBR), fluororubber, or a combination thereof. The binder may be in the form of colloidal particles, in particular.

[0021] The binder may be a material that has a high affinity with the fibrous material. For example, when the fibrous material is a material formed by a six-membered ring network such as CNT, it is considered that the fibrous material can capture the binder more efficiently by π-π interaction when a material having an aromatic ring such as SBR is used as the binder.

[0022] The content of the binder may be 10 parts by mass or more, 15 parts by mass or more, 25 parts by mass or more, or 30 parts by mass or more, and may be 50 parts by mass or less, 40 parts by mass or less, 35 parts by mass or less, or 33 parts by mass or less, relative to 100 parts by mass of the electrode mixture.

[0023] The mass ratio of the fibrous material to the binder in the electrode mixture may be 1:3000 to 1:6000, 1:3500 to 1:5500, or 1:4000 to 1:5000.

[0024] The dispersion medium is not particularly limited as long as it can disperse the fibrous material and the binder. For example, the dispersion medium may be water, and an organic solvent such as N-methylpyrrolidone and acetone, but is not limited thereto.

[0025] The method of mixing the fibrous material and the binder in the dispersion medium is not particularly limited, but may be, for example, a method of kneading with a kneader. In this case, the shear rate may be more than 0 rpm, 1 rpm or more, 3 rpm or more, or 5 rpm or more, and may be 300 rpm or less, 200 rpm or less, 100 rpm or less, or 50 rpm or less. In addition, the kneading time may be more than 0 minutes, 1 minute or more, 3 minutes or more, or 5 minutes or more, and may be 60 minutes or less, 30 minutes or less, 20 minutes or less, or 10 minutes or less.

[0026] <Electrode mixture slurry preparation process> The method of the present disclosure includes mixing the resulting pre-slurry and an electrode active material to obtain an electrode mix slurry.

[0027] For purposes of this disclosure, "electrode mix slurry" means a slurry that includes a dispersion medium in addition to an "electrode mix" and that can be applied and dried to form an electrode active material layer.

[0028] The electrode active material is not particularly limited as long as it can be used as an electrode active material of a battery. Therefore, the electrode active material may be either a positive electrode active material or a negative electrode active material. Among known electrode active materials, two materials having different potentials (charge / discharge potentials) at which a specific ion is absorbed and released can be selected, and the material showing a more noble potential can be used as a positive electrode active material, and the material showing a less noble potential can be used as a negative electrode active material.

[0029] As the positive electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Various lithium-containing composite oxides such as lithium manganate, lithium spinel compounds, etc. can be used. Lithium iron phosphate (LFP) can be used as an olivine-type positive electrode active material. The positive electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.

[0030] As the negative electrode active material, a known active material may be used. For example, in the case of constructing a lithium ion battery, the negative electrode active material may be a silicon-based active material such as silicon, a silicon alloy, or silicon oxide; a carbon-based active material such as graphite or hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, a lithium alloy, or the like. The negative electrode active material may be, for example, particulate, and the size of the particulate is not particularly limited.

[0031] In the present disclosure, the electrode active material is particularly used as a negative electrode active material.

[0032] The content of the electrode active material may be 50 parts by mass or more, 55 parts by mass or more, 60 parts by mass or more, or 65 parts by mass or more, and may be 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, or 75 parts by mass or less, relative to 100 parts by mass of the electrode mixture.

[0033] <Drying process> The method of the present disclosure includes applying the resulting electrode mixture slurry to a substrate and drying to remove the dispersion medium.

[0034] The substrate is not particularly limited, but may be a current collector foil that constitutes an electrode together with an electrode active material layer.

[0035] The current collector foil is not particularly limited as long as it can be used as a current collector foil for a battery. For example, when forming a lithium ion battery, it may be an aluminum foil or a copper foil.

[0036] The method for applying the electrode mixture slurry to the substrate is not particularly limited, but may be, for example, a blade coating method.

[0037] The method of drying and removing the dispersion medium is not particularly limited. For example, the heat source in the drying process may be hot air or a laser. The drying temperature and drying time may be determined arbitrarily depending on the boiling point of the dispersion medium used, etc.

[0038] In an electrode active material layer produced by the method of the present disclosure, a method for confirming that the binder is entangled and captured by the fibrous material can be, for example, a method of obtaining and observing an image of the electrode active material layer using a scanning electron microscope (SEM).

[0039] In an electrode active material layer produced by the method of the present disclosure, a method for confirming that the binder is uniformly dispersed in the electrode active material layer can be exemplified by obtaining a cross-sectional SEM image of the electrode active material layer and observing the degree of dispersion of the binder.

[0040] Also, for example, the degree of dispersion of the binder in the electrode active material layer can be quantified by the following method. That is, first, the acquired cross-sectional SEM image is imported into image processing software (Image J) and quantified. The digital image data is in the form of a matrix corresponding to the cross-sectional SEM image of the electrode active material layer, and a numerical value is assigned to each pixel. This numerical value is expressed in 256 gradations, which is 2 to the power of 8, in 8-bit display, and takes integer values ​​from 0 to 255, but this is binarized and expressed as 0 and 1. The binarization is performed by counting the numerical values ​​displayed from 0 to 255, and the numerical values ​​in the top 10% are set to "1" and the other numerical values ​​are set to "0". Next, the binarized numerical values ​​are added for each row to calculate the total value of each row. Furthermore, the total values ​​of each row are added for the rows corresponding to the upper half of the electrode active material layer in the thickness direction. This is called the "total value in the upper half of the electrode active material layer". Similarly, the "total value in the lower half of the electrode active material layer" is calculated. Based on these, the degree of dispersion of the binder in the electrode active material layer can be quantified by the following formula, which is defined as the "binder dispersion index": Binder dispersion index=total value in the upper half of the electrode active material layer÷total value in the lower half of the electrode active material layer (1).

[0041] The dispersion index of the binder may be 1.00 or more, 1.05 or more, 1.10 or more, or 1.15 or more, and may be less than 1.90, 1.80 or less, 1.70 or less, 1.60 or less, 1.50 or less, 1.40 or less, 1.30 or less, or 1.20 or less.

[0042] The smaller the dispersion index of the binder, the more uniformly the binder is dispersed in the electrode active material layer.

[0043] <Battery manufacturing method> The method of manufacturing a battery according to the present disclosure includes manufacturing an electrode active material layer by the method of the present disclosure. For the method of manufacturing an electrode active material layer, reference can be made to the above description of the method of manufacturing an electrode active material layer according to the present disclosure.

[0044] The method of the present disclosure for producing a battery may include, in addition to producing an electrode active material layer, arranging an anode current collector layer, an anode active material layer, an electrolyte layer, a cathode active material layer, and a cathode current collector layer in this order. In this case, either or both of the anode active material layer and the cathode active material layer may be an electrode active material layer produced by the method of the present disclosure. EXAMPLES

[0045] Example 1 <Formation of Electrode Active Material Layer> (Preliminary slurry preparation process) 0.01 parts by mass of single-walled carbon nanotubes (SWCNTs) (average diameter 20 nm) as a fibrous material, a 3% aqueous solution of styrene-butadiene rubber (SBR)-based binder (45 parts by mass as SBR), and water as a dispersion medium were placed in a kneader and kneaded at a shear rate of 10 rpm for 30 minutes to obtain a preliminary slurry.

[0046] (Electrode mixture slurry preparation process) 96.6 parts by mass of graphite as a negative electrode active material, 0.4 parts by mass of carboxymethylcellulose (CMC) as a dispersant, and water as a dispersion medium were placed in a kneader other than that used for preparing the above preliminary slurry, and kneaded at a shear rate of 10 rpm for 30 minutes. This kneaded material was kneaded with the above preliminary slurry to obtain an electrode composite slurry.

[0047] (drying process) The obtained electrode mixture slurry was applied to a substrate and the dispersion medium in the slurry was dried and removed by irradiating with a laser, thereby forming an electrode active material layer of Example 1.

[0048] Comparative Example 1 The electrode active material layer was formed as follows without preparing a preliminary slurry. That is, first, 96.6 parts by mass of graphite as a negative electrode active material and 0.4 parts by mass of CMC as a dispersant were kneaded to obtain a kneaded material. Next, 0.01 parts by mass of SWCNT as a fibrous material and water as a dispersion medium were kneaded with the kneaded material to obtain a slurry. Furthermore, a 3% aqueous solution of SBR-based binder (45 parts by mass of SBR) and water as a dispersion medium were kneaded with the slurry to obtain an electrode mixture slurry. The kneading conditions were the same as in Example 1. The dispersion medium of the obtained electrode mixture slurry was dried in the same manner as in Example 1 to form an electrode active material layer of Comparative Example 1.

[0049] "evaluation" Evaluation using SEM images Scanning electron microscope (SEM) images of the electrode active material layer of each example were obtained to evaluate the degree of capture of the binder by the fibrous material.

[0050] Evaluation using cross-sectional SEM images A cross-sectional SEM image of the electrode active material layer of each example was obtained, and the degree of dispersion of the binder in the electrode active material layer was observed.

[0051] In addition, the degree of dispersion of the binder in the electrode active material layer was quantified by the following method. That is, first, the acquired cross-sectional SEM image was imported into image processing software (Image J) and quantified. The digital image data is in the form of a matrix corresponding to the cross-sectional SEM image of the electrode active material layer, and a numerical value is assigned to each pixel. This numerical value is displayed in 256 gradations, which is 2 to the power of 8, in 8-bit display, and takes integer values ​​from 0 to 255, but this was binarized and expressed as 0 and 1. The binarization was performed by counting the numerical values ​​displayed from 0 to 255, and the numerical values ​​in the top 10% were set to "1" and the other numerical values ​​were set to "0". Next, the binarized numerical values ​​were added for each row to calculate the total value of each row. Furthermore, the total values ​​of each row were added for the row corresponding to the upper half of the thickness direction of the electrode active material layer. This was defined as the "total value in the upper half of the electrode active material layer". Similarly, the "total value in the lower half of the electrode active material layer" was calculated. Based on these, the degree of dispersion of the binder in the electrode active material layer was quantified by the following formula, which was taken as the dispersion index of the binder: Binder dispersion index=total value in the upper half of the electrode active material layer÷total value in the lower half of the electrode active material layer (1).

[0052] "result" <Evaluation results based on SEM images> SEM images of the electrode active material layer of each example are shown in Figure 2. As shown in Figure 2(a), in the electrode active material layer formed by the method of the example, it was confirmed that SBR as a binder was trapped in CNT as a fibrous material. In contrast, as shown in Figure 2(b), in the electrode active material layer formed by the method of the comparative example, it was not confirmed that SBR as a binder was trapped in CNT as a fibrous material.

[0053] <Evaluation results based on cross-sectional SEM images> Cross-sectional SEM images of the electrode active material layer of each example are shown in Figure 3. As shown in Figure 3(a), in the electrode active material layer formed by the method of the example, it was confirmed that the SBR as a binder was uniformly dispersed throughout the electrode active material layer. In contrast, as shown in Figure 3(b), in the electrode active material layer formed by the method of the comparative example, it was confirmed that the SBR as a binder was unevenly distributed on the surface side of the electrode active material layer.

[0054] The dispersion index of the binder calculated by the above formula (1) was 1.17 for the electrode active material layer of Example 1, and 1.90 for the electrode active material layer of Comparative Example 1. [Explanation of symbols]

[0055] 1. Electrode mixture slurry 10 Fibrous materials 20. Binder 30 Electrode active material 40 Dispersion medium 50 Base material

Claims

1. A method for producing an electrode active material layer, comprising the steps of: mixing the fibrous material and the binder in a dispersion medium to obtain a preliminary slurry; Mixing the obtained preliminary slurry and an electrode active material to obtain an electrode mixture slurry; and The obtained electrode mixture slurry is applied to a substrate, and the dispersion medium is then dried to remove it.

2. The fibrous material is a carbon nanotube. The method of claim 1.

3. The binder is a styrene butadiene rubber. The method of claim 2.

4. The method according to claim 1 , wherein the heat source in the drying step is hot air or a laser.

5. A method for producing a battery, comprising producing an electrode active material layer by the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Positive electrode for secondary battery and secondary battery comprising the same

    JP2021007109A

  • Electrode, rechargeable battery, battery pack, and vehicle

    JP2021044216A

  • Carbon nanotube dispersion liquid for electrode slurry, negative electrode slurry, nonaqueous electrolyte secondary battery, and manufacturing method for carbon nanotube dispersion liquid for electrode slurry

    WO2022138108A1

  • Electrode material, electrode material manufacturing method, and battery

    WO2022249589A1

  • Negative electrode and method for manufacturing the same

    JP2023522659A